Traditional water harvesting structure: community behind `community' - Kashwan, Prakash (2006)
The work of Tarun Bharat Sangh in Rajasthan has received much attention. There is an unrgent need though to question development challenges that go overboard in extolling the virtues of greenery without tracing the hands that own'the land and harvest the fruits of public money. - Reproduced.
Keywords: Water